THE DEVELOPMENT OF SPEAKING SKILLS IN ARABIC LANGUAGE LEARNING IN INDONESIA: A LITERATURE REVIEW - Attruk, Muhammad Fariq Heemal (EDUCATUM: Scientific Journal of Education, 2025)
This study examines the relationship between teachers’ communicative competence and the development of maharah kalam (Arabic speaking skills) in the context of Arabic language instruction in Indonesia. Using a Narrative Literature Review (NLR) approach, the study synthesizes empirical and conceptual works published between 2014 and 2025, including selected foundational theoretical works, to identify thematic trends, theoretical orientations, and research gaps. The findings indicate that teachers’ communicative competence constitutes an essential professional foundation; however, its influence on students’ speaking development is neither direct nor linear. Rather than operating as an isolated variable, teacher competence functions through mediating mechanisms. The literature consistently suggests that communicative classroom interaction and the intensity of language practice serve as key linking variables between teacher competence and the development of speaking skills. When instruction provides sustained opportunities for dialogic exchange, contextual oral production, simulation, and repeated speaking practice, improvements in fluency, confidence, and performative speaking outcomes become more evident. Conversely, structurally oriented and teacher-centred approaches tend to restrict meaningful language use and limit communicative development. Based on this synthesis, the study proposes a conceptual mediation model linking teacher communicative competence, interaction quality, intensity of language practice, and the development of maharah kalam. The review also identifies a significant research gap, namely the limited operationalization of teacher communicative competence as a measurable linguistic construct, and calls for future experimental, longitudinal, or mediation-based studies to provide stronger causal evidence in the Indonesian context.